Perception thresholds for augmented reality navigation schemes in large distances - Tonnis, Marcus; Klein, Leslie; Klinker, Gudrun (2008 7th IEEE International Symposium on Mixed and Augmented Reality, 2008)
Because the resolution of see-through displays is lower than the resolution of the human eye, perception of AR schemes is complicated in large distances. To discover, how design issues of perception correlate with presentation in large distances, we developed three different variants of arrow-based route guidance systems. With a large-scale Head-Up Display having a large focal depth, we tested the variants under different conditions on perception and interpretability.